Lisey's story eaudiobook A novel. - King, Stephen (Simon & Schuster Audio, 2006)
*Now an Apple TV+ limited series starring Julianne Moore and Clive Owen* The "haunting...tender, intimate book that makes an epic interior journey" ( The New York Times ), Lisey's Story is a literary masterpiece—an extraordinarily moving and haunting portrait of a marriage and its aftermath. Lisey lost her husband Scott, after a twenty-five year marriage of profound and sometimes frightening intimacy. Scott was an award-winning, bestselling novelist and a very complicated man. Early in their relationship, Lisey knew there was a place Scott went that both terrified and healed him, could eat him alive or give him the ideas he needed in order to live. Now it's Lisey's turn to face Scott's demons, to go to that terrifying place known as Boo'ya Moon. What begins as a widow's effort to sort through the papers of her celebrated husband becomes a nearly fatal journey into the darkness he inhabited. "Intricate...exhilarating" ( The New Yorker ), perhaps Stephen King's most personal and powerful novel ever, Lisey's Story is about the wellsprings of creativity, the temptations of madness, and the secret language of love. It is a beautiful, "rich portrait of a marriage, and the complicated affection that outlives death" ( The Washington Post ).